The Betrayed Generation? Intra-Household Transfers and Retirement Behavior in South Korea - Kyeongkuk Kim; Sang-Hyop Lee; Timothy J. Halliday (Institute of Labor Economics (IZA), 2018)
We consider the nexus of intra-household transfers, the sex composition of the sibship, and parental retirement behavior in Korea. We provide evidence that the cost of raising sons is higher than it is for daughters in Korea. Thus, in the absence of sufficient transfers from adult sons to parents, parents will fund their earlier investments in their sons by increasing their labor supply. Consistent with this, we show that parents with more adult sons delay their retirement. In particular, an elderly parent with all sons has a retirement probability that is 7–10 percentage points lower than a comparable parent with all daughters. Elderly parents also work between 1.8 and 2.7 hours more per week when their sibship consists of all sons. These effects are the most pronounced when the first born is a son, as well as for poorer households.
Keywords: J1; J13; J16; J26; 330; retirement; intra-household transfers; gender; sex ratios